State of the art and prospects of chemically and thermally aggressive membrane gas separations: Insights from polymer science. (16th August 2021) - Deng, Jing; Huang, Zihan; Sundell, Benjamin J.; Harrigan, Daniel J.; Sharber, Seth A.; Zhang, Ke; Guo, Ruilan; Galizia, Michele
Abstract: Membrane gas separation at high temperatures and in the presence of aggressive chemicals, such as H2 S, NH3, SOx, NOx and hot water vapor, is attracting interest from both a fundamental and industrial standpoint. To fully exploit the benefits of membrane technology, it is imperative to develop membrane materials that withstand thermally and chemically harsh conditions, as well as to understand the fundamental principles underpinning the transport of aggressive species in polymer membranes. In this paper, we review the state of the art of membrane separations in thermally and chemically aggressive environments, with emphasis on polymer membranes and polymer-based mixed matrix membranes. Guidelines for membrane materials selection in thermally and chemically aggressive environments are provided, major roadblocks to progress in the field are discussed, and possible strategies to remove such roadblocks are proposed. Research needs are identified and recommendations for future research directions in the field are provided. Finally, to put in broad perspective the performance of the most promising literature materials, selectivity-permeability upper bounds in the presence of complex gas mixtures containing aggressive species and in a wide temperature range are shown and discussed. Graphical abstract: Image 1 Highlights: Membrane gas separation in the presence of aggressive species is reviewed. Membrane gas separation at high temperature is reviewed. Upper bounds for complex mixtures and at high T are shown and discussed. Membrane materials design in aggressive environments is discussed.